2011
DOI: 10.1155/2011/367364
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Actinomycosis

Abstract: Nasopharyngeal actinomycosis is a rarely encountered bacterial infection which usually occurs after nasal trauma or surgery. In some clinical cases, nasopharyngeal actinomycosis has appeared in patients without prior trauma, making diagnosis difficult. Here we present three such cases successfully treated with appropriate dosages of penicillin. One 16-year-old boy with no previous medical antecedents showed an important thickening of the posterior wall of the nasopharynx. A similar nasopharyngeal thickening wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Studies on actinomycosis in the nasopharynx are extremely rare, and most reported cases occurred in the posterior wall. 2-10 This report presents a case of actinomycosis in the Rosenmüller’s fossa.…”
Section: Introductionmentioning
confidence: 97%
“…Studies on actinomycosis in the nasopharynx are extremely rare, and most reported cases occurred in the posterior wall. 2-10 This report presents a case of actinomycosis in the Rosenmüller’s fossa.…”
Section: Introductionmentioning
confidence: 97%
“…Actinomyces species are normal commensal bacteria that can be found in the oral cavity and the lower reproductive tract of women [ 1 ]. The bacteria are Gram-positive, filamentous, non-acid-fast, and anaerobic-to-microaerophilic [ 2 ]. This species is pathogenic but nonvirulent, so infection is often opportunistic leading to actinomycosis which is a rare subacute-to-chronic infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This species is pathogenic but nonvirulent, so infection is often opportunistic leading to actinomycosis which is a rare subacute-to-chronic infection [ 3 ]. Actinomycosis is characterised by localised spread via abscess and sinus tracts with granulomatous inflammation [ 2 ]. Due to this propensity for local spread, identified infections should be investigated for deep sources which may contribute to an ongoing insidious clinical source or may be mistaken for other pathologies such as carcinomas [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Actinomyces, the causative organism, is a gram-positive, branching and filamentous bacterium. [ 3 ] It is often a commensal inhabiting oropharynx, gastrointestinal and urogenital tract. [ 4 ] Healthy people usually get infected after a mucosal trauma or inoculation into an anaerobic environment.…”
mentioning
confidence: 99%
“…There was a decrease in the incidence of actinomycosis after the introduction of broad-range antibiotics and maintaining good oral hygiene. [ 3 ] In late presentation or delay in diagnosis, they can present as an invasive lesion with surrounding tissue destruction. These can mimic either as a malignant lesion or chronic infective lesions like tuberculosis or fungal infection.…”
mentioning
confidence: 99%